SOSIALISASI PEMAHAMAN DAN PENDAMPINGAN PEMBUATAN IZIN USAHA UMKM DESA SUMBERSARI - Mutmainah, Latifah; Juliandara, luthpiyah; Iskandar, Tatang (Universitas Islam 45 Bekasi, 2023)
The Implementation of community service aims to provide Understanding and assistance in training for the creation of licensed integrated bussiness OSS managed by the goverment in the coordination of invesment services and one-step integrated services (DPMPTSP) aimed at NIB benefits and stucturing administrative order. The method used in research is socialization through lectures, discussion between participants and practice. The conseling approach is semi-formal and relevant according to community needs as well as stuctured explanation in language that is easy to understand. Apart from that , the sources are appropriate to their field of expertise because they are members who are sent directly by the goverment agency that works in the village. The couseling is presented interactively and includes a question and answer session. The result obtained bring benefits and insight to the local community and MSMEs as well as a reference for readers or writers with the subtitle regarding counseling on making bussiness permits (NIB).